Integrasi Know-Want-Learned-Affect (KWLA) Dalam Pembelajaran Teks Anekdot Sebagai Penguatan Intrapersonal Intellegence - Ermawati Ermawati (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2017)
This article aims to integrate the (KWLA) strategy in learning the annecdote texts as a as part of intrapersonal intelligence reinforcement. The KWLA strategy consists of four columns (What I Already Know-What I Want To Know-What I Learned - The Affect of The Story) is implemented to needed to help students understand the the contents of annecdote texts easily. In the KWLA column, learners write down what has been known, what they want to know, what has been known after understanding the text, and the effect of the story text. Another expected result, through the affect of the story column (column A) phase in this KWLA, occurs in the enforce the intrapersonal intelligence in the form of personality and empathy in the learners.